2000
DOI: 10.1006/viro.1999.0155
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Cell-to-Cell Movement of Beet Yellows Closterovirus

Abstract: A beet yellows closterovirus (BYV) variant expressing green fluorescent protein and leaves of BYV local lesion host Claytonia perfoliata were used to reveal genetic requirements for BYV cell-to-cell movement in leaf epidermis and mesophyll. A series of mutations targeting genes that are not involved in amplification of the viral positive-strand RNA was analyzed. The products of genes coding for a 6-kDa hydrophobic protein (p6) and a 64-kDa protein (p64), as well as for minor and major capsid proteins, were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
105
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 78 publications
1
105
0
1
Order By: Relevance
“…What is the primary function of p20 in the BYV life cycle? Previous work demonstrated that p20 is dispensable for BYV replication (39) and is not essential for virus cell-to-cell movement, although it might have an accessory role in the latter process (2). The interaction of p20 with Hsp70h, which is one of the three BYV MPs (40), prompted us to revisit the role of p20 in cell-to-cell movement.…”
Section: Resultsmentioning
confidence: 99%
“…What is the primary function of p20 in the BYV life cycle? Previous work demonstrated that p20 is dispensable for BYV replication (39) and is not essential for virus cell-to-cell movement, although it might have an accessory role in the latter process (2). The interaction of p20 with Hsp70h, which is one of the three BYV MPs (40), prompted us to revisit the role of p20 in cell-to-cell movement.…”
Section: Resultsmentioning
confidence: 99%
“…Among the sequences available in protein databases, the corresponding protein of LIYV is the most similar (29.8% amino acid identity) to SPCSV p60. The CTV p61 protein, which corresponds to SPCSV p60, is essential for viral cell-to-cell movement (5) and virion assembly (55).…”
mentioning
confidence: 99%
“…However, the SPCSV CPm was 1.5-fold larger than that of LIYV (52 kDa), due primarily to differences within the N-proximal portions of the proteins. Studies of clostero-and crinivirus particles have revealed that CPm assembles within a 75-to 85-nm stretch at one end of the virus particle (3,21,58,66) and is essential for viral cell-to-cell movement (5,6). LIYV CPm has been implicated in virus transmissibility with the whitefly vector (58).…”
mentioning
confidence: 99%
“…Atomic force microscopy studies demonstrate that the closterovirus virion terminal structure has a complex morphology and consists of three distinct segments, of which the tip segment is likely to be formed by the p20 protein (Peremyslov et al, 2004). Since the CPm, Hsp70h and p64 proteins are required for BYV cell-to-cell movement (Alzhanova et al, 2000;Peremyslov et al, 1999;Prokhnevsky et al, 2002), it has been concluded that the terminal structure represents the specialized device evolved to facilitate translocation of closterovirus virions to and through plasmodesmata . Of these proteins, Hsp70h may be the key element of BYV transport machinery, since this protein, when expressed in the absence of other viral products, is able to localize to motile granules, which are transported to the cell periphery in an actin-dependent manner, and can associate with plasmodesmata (Prokhnevsky et al, 2005).…”
Section: Role Of Virions In Cell-to-cell Transport Of Filamentous Virmentioning
confidence: 99%